Aerobic Microbiological Profile in Vaginal Discharge Syndrome - Mahaseth, Binod Kumar; Malla, Tarka Bahadur (Journal of Nepalgunj Medical College, 2018)
Introduction: Vaginal discharge syndrome consists of abnormal vaginal discharge, vaginal itching, painful urination and painful sexual intercourse, among them abnormal vaginal discharge is one of the most common clinical symptoms for which most of the female seek care for management in gynaecology and obstetrics outpatient department. Abnormal vaginal discharge in the women of reproductive age can lead to subfertility, ectopic pregnancy, early rupture of membrane, chronic pelvic pain and increases susceptibility for HIV virus and oncogenic virus.Objective: To identify aerobic microflora associated with vaginal discharge and find out most useful drugs for it.Material and Methods: A Hospital based cross sectional study was carried out at Nepalgunj Medical College Teaching Hospital, Kohalpur in November 2016 to November 2017. Ninety- five women who were at reproductive age group with vaginal discharge and met inclusion criteria participated in the study. Samples were taken from posterior fornix of vagina with the help of cotton swab following the confirmation of vaginal discharge by per speculum examination, culture and sensitivity was done.Result: The mean age of participants was 32.7±8.1. Out of 95 participant's samples, aerobic vaginal microfloras were grown in 18 (18.94%) participants and 77 (74.73%) samples was found to be sterile. E. coli and staphylococcus aureus (predominant aerobic vaginal flora) was grown in 7(38.88%). E. coli was sensitive with all available antibiotics in majority of samples showed sensitive to ciprofloxacin, ceftriaxone, tobramycin and meropenam i.e 6 (85.71%) each followed by cefixime and cefpodoxime 5(71.42%), least sensitive with doxycycline 4(57.14%).Similarly, in majority of the samples Staphylococcus aureus was also found to be sensitive with doxycycline, ceftriaxone and meropenam 7(100%) each followed by tobramycin in 6(85.71%), ciprofloxacin and cefixime 2 (28.58%), least sensitive with cefpodoxime 1(14.29%). Meanwhile Ciprofloxacin and tobramycin 2(100%) found to be more effective for klebsiella pneumoniae and doxycycline, meropenam, cefixime and cefpodoxime was found to least effective 1(50%). Chloramphenicol was the only drug sensitive to streptococcus in total collected samples. However Acinetobacter was sensitive with ceftriaxone, ciprofloxacin and doxycycline 1(100%) each but resistant with rest of the antibiotics like meropenam, tobramycin, cefixime and cefpodoxime 1(100%). Most microorganisms were found to be sensitive with ceftriaxone, tobramycin and meropenam 14 (77.77%) and was followed by doxycycline 13 (72.22%) and ciprofloxacin in 11 (61.11%). Cefpodoxime 11(61.11%) and cefixime10 (55.55%), they found poorly in sensitivity test.Conclusion: Bacterial culture and its sensitivity in vaginal discharge should be done not only because of its troublesome symptoms but for its complications like subfertility, preterm delivery, ectopic pregnancy and it's increased susceptibility for HIV and oncogenic virus. E. coli and staphylococcus were the predominant bacteria found in present study and were followed by klebsiella pneumoniae, streptococcus and acinetobacter. In this study, Ceftriaxone (85.7%) and meropenam (100%) were found to be more effective for E.coli and staphylococcus aureus respectively, ciprofloxacin could be used as a choice of drugs for E.coli (sensitivity 85.7%). However for staphylococcus, doxycycline was a better option with 100 % sensitivity.